The Influence of Perceived Organizational Support and Work Environment on Turnover Intention (Study on Millennial Employees in West Java) - Kinasih, Florentina Tri; Indiyati, Dian (UNIVERSITAS PAKUAN, 2019)
This research intends to find out the influence of perceived organizational support also work environment on turnover intention in millennial employees of the textile industry in West Java. The method used is quantitative. The questionnaires were distributed to 120 respondent in order to collect the data. Then, the data were analyzed using descriptive analysis techniques also path analysis using IBM SPSS Version 26. The findings indicated a significant and simultaneous influence on the organizational support perception also work environment on turnover intention. The total impact of perceived organizational support also work environment on changes in turnover intention level is 30% also 31.2%, respectively.